Pengembangan Aplikasi Clipboard Salin Tempel Karakter Teks dari Citra Digital - Muhammad Evan Arnanda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This study aims to build software that can perform text extraction on an image containing text. This research uses a software development method called incremental. The application is built using the Python programming language and the use of Tesseract as a model. The output of this application is in the form of text that is put into the clipboard so that the user can paste the output into the preferred place. This research produces an application that can perform text extraction on an image containing text. This application was tested using black box testing, from several tests on the available features, all test results were successful because the features tested could function and be used.